2018
DOI: 10.1186/s12967-018-1425-7
|View full text |Cite
|
Sign up to set email alerts
|

The selective cathepsin K inhibitor MIV-711 attenuates joint pathology in experimental animal models of osteoarthritis

Abstract: BackgroundMIV-711 is a highly potent and selective cathepsin K inhibitor. The current article summarizes the therapeutic effects of MIV-711 on joint pathology in rabbits subjected to anterior cruciate ligament transection (ACLT), and the prophylactic effects on joint pathology in dogs subjected to partial medial meniscectomy, two surgical models of osteoarthritis (OA).MethodsStarting 1 week after surgery, rabbits were dosed daily via oral gavage with either MIV-711 or vehicle (n = 7/group) for 7 weeks. The fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 45 publications
(57 reference statements)
1
33
0
1
Order By: Relevance
“…The CTX-II data suggests that MIV-711 may be useful in reducing subchondral bone turnover and attenuating cartilage disease progression in OA patients. Indeed, MIV-711 has demonstrated protective effects on subchondral bone and articular cartilage in nonclinical disease models [ 40 ] at exposures that are in the same range as reported in this study. Additionally, recent clinical data from a Phase II study with MIV-711 in knee OA patients, given once daily for 6 months, demonstrated benefit on joint structure, with significantly lower increases in bone area and cartilage thinning in the diseased knee, as assessed by magnetic resonance imaging (MRI), compared to patients who received placebo [ 24 ].…”
Section: Discussionsupporting
confidence: 57%
“…The CTX-II data suggests that MIV-711 may be useful in reducing subchondral bone turnover and attenuating cartilage disease progression in OA patients. Indeed, MIV-711 has demonstrated protective effects on subchondral bone and articular cartilage in nonclinical disease models [ 40 ] at exposures that are in the same range as reported in this study. Additionally, recent clinical data from a Phase II study with MIV-711 in knee OA patients, given once daily for 6 months, demonstrated benefit on joint structure, with significantly lower increases in bone area and cartilage thinning in the diseased knee, as assessed by magnetic resonance imaging (MRI), compared to patients who received placebo [ 24 ].…”
Section: Discussionsupporting
confidence: 57%
“…Consequently, CatK is currently among the promising therapeutic target candidates for the development of disease-modifying osteoarthritic drugs. It is encouraging to learn that CatK inhibition could exert obvious chondroprotective effect in preclinical OA models (Connor et al, 2009;McDougall et al, 2010;Hayami et al, 2012;Lindstrom et al, 2018). Furthermore, a novel selective CatK inhibitor MIV-711 by Medivir was recently reflected to reduce bone remodeling and cartilage volume loss but have no impact on pain in OA patients in a Phase-IIa trial (Conaghan et al, 2019).…”
Section: Catk and Skeletal Diseasesmentioning
confidence: 99%
“…OA is the most common joint disease characterized by progressive cartilage degeneration, changes in the subchondral bone, and chronic synovitis [ 1 , 2 , 3 ]. Modern treatment of OA is limited to the use of drugs that affect the symptoms of the disease: analgesics, anti-inflammatory drugs, and devices for treatment [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%